Enhanced healing efficacy of an optimized gabapentin-melittin nanoconjugate gel-loaded formulation in excised wounds of diabetic rats - Hani Z. Asfour; Nabil A. Alhakamy; Osama A. A. Ahmed; Usama A. Fahmy; Shadab Md; Mohamed A. El-Moselhy; Waleed Y. Rizg; Adel F. Alghaith; Basma G. Eid; Ashraf B. Abdel-Naim (Taylor & Francis Group, 2022)
The present study aimed to design and optimize, a nanoconjugate of gabapentin (GPN)-melittin (MLT) and to evaluate its healing activity in rat diabetic wounds. To explore the wound healing potency of GPN-MLT nanoconjugate, an in vivo study was carried out. Diabetic rats were subjected to excision wounds and received daily topical treatment with conventional formulations of GPN, MLT, GPN-MLT nanoconjugate and a marketed formula. The outcome of the in vivo study showed an expedited wound contraction in GPN-MLT-treated animals. This was confirmed histologically. The nanoconjugate formula exhibited antioxidant activities as evidenced by preventing malondialdehyde (MDA) accumulation and superoxide dismutase (SOD) and glutathione peroxidase (GPx) enzymatic exhaustion. Further, the nanoconjugate showed superior anti-inflammatory activity as it inhibited the expression of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). This is in addition to enhancement of proliferation as indicated by increased expression of transforming growth factor-β (TGF- β), vascular endothelial growth factor-A (VEGF-A) and platelet-derived growth factor receptor-β (PDGFRB). Also, nanoconjugate enhanced hydroxyproline concentration and mRNA expression of collagen type 1 alpha 1 (Col 1A1). In conclusion, a GPN-MLT nanoconjugate was optimized with respect to particle size. Analysis of pharmacokinetic attributes showed the mean particle size of optimized nanoconjugate as 156.9 nm. The nanoconjugate exhibited potent wound healing activities in diabetic rats. This, at least partly, involve enhanced antioxidant, anti-inflammatory, proliferative and pro-collagen activities. This may help to develop novel formulae that could accelerate wound healing in diabetes.